Ligand recognition and signal transduction by lectin receptor-like kinases in plant immunity - Liu, Lu; Liu, Jun; Xu, Ning (Frontiers in Plant Science, 2023)
Lectin receptor-like kinases (LecRKs) locate on the cell membrane and play diverse roles in perceiving environmental factors in higher plants. Studies have demonstrated that LecRKs are involved in plant development and responses to abiotic and biotic stresses. In this review, we summarize the identified ligands of LecRKs in Arabidopsis, including extracellular adenosine triphosphate (eATP), extracellular nicotinamide adenine dinucleotide (eNAD+), extracellular NAD+ phosphate (eNADP+) and 3-hydroxydecanoic acid (3-OH-C10:0). We also discussed the post-transcriptional modification of these receptors in plant innate immunity and the perspective of the future research for plant LecRKs.